Flotation control in an emerging stock market - Castañeda Ramos, Gonzalo (Estudios Económicos de El Colegio de México, 2000)
This paper presents a model to explain the reduced flotation observed in emerging stock markets. It is argued that there is a “rejection effect” when a firm decides to diminish equity fragmentation if it foresees that other firms might increase their stock offerings. Therefore, entrepreneurs, by limiting market size, are capable of keeping their capacity to manipulate prices in the near future. Moreover, the model explains why stock markets grow only temporarily, since their development stops once expectations on market size become more favorable.